Performance of Mule Ducks as Meat Producer and Their Problems - Argono Rio Setioko (Indonesian Center for Animal Research and Development, 2003)
Mule duck, a crossing between muscovy and common duck has a potential as a meat producer. Muscovy and common ducks are available in the villages throughout the country and they have not been utilized optimally for meat production. Mule duck in the villages is a crossing naturally between local drake and muscovy duck. Commercially this duck can be developed through intermating between muscovy drake and common ducks using artificial insemination technique, since the differences in the body size and natural mating resulted in low fertility. In Taiwan, mule ducks (crossing between muscovy and Pekin duck) have been commercially managed and this duck could reach 4 kg at 9 week of age. Beside fast growing bird, mule ducks have better carcass quality (bigger brest meat and low fat) compared to common duck and muscovy. In France, mule ducks are generally used to produce fatty liver that is very common food. To produce bigger fatty liver, it needs mule duck weight ranges from 4.1 to 4.2 kg at 12 weeks. Fatty liver obtained from mule ducks was reported to be 702 grams compared to 560 grams from muscovy and 793 grams from swan. Nervertheless, fertility is one of the major problems. It was reported that fertility rate was only about 40%. In addition, the dark collor of feathers makes the collor of carcass becomes unattractive. Both problems could be overcome through intensive and continued selection programmes. Key words: Mule, meat, duck, muscovy